Metabolic syndrome. Issue 6 (June 2013) - Lawrence, Clare; Lawrence, Matthew
Metabolic syndrome is the term given to a cluster of cardiovascular disease risk factors that includes hyperinsulinaemia, low glucose tolerance, hypertension, central obesity and dyslipidaemia. Syndrome X, also known as Reaven's syndrome, was first defined as a condition in which insulin resistance underpinned the other cardiovascular risk factors of glucose intolerance, hyperinsulinaemia, dyslipidaemia and hypertension. Obesity was not included in this definition; but as this often precedes the initial development of insulin resistance, this has been added to the definition and syndrome X has evolved into the concept of metabolic syndrome. Metabolic syndrome is important because of the increased risk that sufferers have of developing type 2 diabetes, as well as other cardiovascular conditions, including coronary heart disease and stroke, and is a useful predictor of patients predisposed to these disorders. The GP has a key role in the early identification of those patients with metabolic syndrome and the prompt initiation of treatment to prevent these patients developing complications.